Apropriação das áreas de pesca e uso dos recursos pesqueiros da Lagoa Mangueira por pescadores artesanais - Santos, Jackes Douglas Manke dos (2012)
The Lagoa Mangueira located in southern Brazil is part of a complex river system of the coastal plain of Rio Grande do Sul, in the presence of extensive wetlands, owned by the lagoon system belonging to known as Patos-Mirim. It has inhabited and exploited human populations, and the fishing one of the most important activities. The fishing activity developed in the region has decreased capture rates, as declared by fishermen, causing them to continuous intensification and diversification of their capture techniques. The objective of this study was to characterize the occupation process the Lagoa Mangueira by artisanal fishermen, the composition and quantity of fish caught, and to describe the fishermen behavior against the fish abundance variation. For the identification of fishing communities, field trips were held monthly in the years 2010 and 2011. Semi-structured interviews were conducted on sampling method known as chain of informants. Fish catch data were provided by local fishermen, through their writings, which were tabulated and submitted to descriptive statistics. The first forays into the fishing in Lagoa Mangueira were made in the early 1960s. Currently there are seven fishermen core on the west bank of the lagoon. The entry of new fishermen obey the general criteria for the establishment of traditional communities. The average catch per fisherman in the region is 4766.5 kg / year, and the viola (Loricariichthys anus) is the species with the highest volume of capture and that provides greater economic income of the local fisheries. It demonstrated the importance of participation and inclusion of these agents in the development and implementation of public politics for management and conservation of natural resources in the region, since these populations are in possession of accurate information on the ecosystem.